A critical analysis of the role played by the Presbyterian Church in Cameroon in addressing the political crisis in Cameroon, 1990 – 1992 - Pillay, Jerry (University of Pretoria, 2024)
Thesis (PhD (Systematic and Historical Theology))--University of Pretoria, 2023.